Design and Testing of a Spherical Autonomous Underwater Vehicle for Shipwreck Interior Exploration - Ross Eldred; Johnathan Lussier; Anthony Pollman (Journal of Marine Science and Engineering, 2021)
This article details the design, construction and implementation of a novel, spherical unmanned underwater vehicle (UUV) prototype for operations within confined, entanglement-prone marine environments. The nature of shipwreck interiors, the exploration of which the vehicle was originally designed, imposes special risks that constrain system requirements while promoting other attributes uncommon in typical open-water UUV designs. The invention, the Wreck Interior Exploration Vehicle (WIEVLE), was constructed using 3-D additive manufacturing technology combined with relatively inexpensive commercial components. Similar inventions are compared, followed by a thorough review of the physical and functional characteristics of the system. The key attributes of the design include a smooth, spherical hull with 360-degree sensor coverage, and a fixed, upward-angled thruster core, relying on inherent buoyancy to take the place of a dedicated depth-changing mechanism. Initial open-loop control testing demonstrated stable 4 degrees of freedom (DOF) maneuvering capability. The article concludes with an overview of the results of the initial testing, a review of how the key system design attributes address the unique shipwreck interior exploration challenges, and a plan for the future development of the platform.